1995
DOI: 10.1016/0042-6989(94)00194-q
|View full text |Cite
|
Sign up to set email alerts
|

Speed discrimination of motion-in-depth using binocular cues

Abstract: Although it is well known that motion-in-depth can be detected using binocular cues, it is not known whether those cues can be used to judge the speed of an object moving in depth. There are at least two possible binocular cues that could be used by the visual system to calculate three dimensional (3-D) speed: the rate of change of binocular disparity, or a comparison of the speeds of motion in the two eyes. We tested which of these cues is used to discriminate the speed of motion-in-depth. First, speed discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 25 publications
10
83
3
Order By: Relevance
“…8B) shows that sensitivity for 2D direction discrimination was several times higher than equivalent 3D motion sensitivities across all eccentricity and motion cue conditions. This replicates stereomotion suppression (Tyler 1971) and supports a larger body of research that has shown that IOVD performance cannot be explained on the basis of monocular stimulation (e.g., Brooks and Stone 2006;Harris and Watamaniuk 1995;Rokers et al 2008;Shioiri et al 2000).…”
Section: Distinguishing the Contributions Of The CD And Iovd Cuessupporting
confidence: 75%
See 1 more Smart Citation
“…8B) shows that sensitivity for 2D direction discrimination was several times higher than equivalent 3D motion sensitivities across all eccentricity and motion cue conditions. This replicates stereomotion suppression (Tyler 1971) and supports a larger body of research that has shown that IOVD performance cannot be explained on the basis of monocular stimulation (e.g., Brooks and Stone 2006;Harris and Watamaniuk 1995;Rokers et al 2008;Shioiri et al 2000).…”
Section: Distinguishing the Contributions Of The CD And Iovd Cuessupporting
confidence: 75%
“…For example, we used a 2AFC direction-discrimination task. We selected this task because it seemed most analogous to a particularly well-studied task in the 2D motion literature (i.e., Newsome and Paré 1988;Watamaniuk et al 1995), but prior work has (understandably) investigated 3D motion perception using a variety of different tasks, including direction estimation, speed discrimination, judging time to contact, and indicating whether motion through depth is perceived (Brooks and Stone 2006;Harris and Dean 2003;Harris and Watamaniuk 1995;PortforsYeomans and Regan 1996). Because each of these tasks might require the observer to rely on and interpret 3D motion signals in different ways-ways that we do not yet fully understand-it is difficult to generalize or compare results across tasks.…”
Section: Relation To Past Workmentioning
confidence: 99%
“…18 -20 S3D viewing often entails tracking a visual object through space and depth, and binocular disparity provides critical visual cues for detecting motion in depth. 21,22 As such, stereoscopic viewing likely affords greater motion perception than 2D viewing and, hence, induces greater motion sickness symptoms due to a heightened conflict between vision and other senses.…”
mentioning
confidence: 99%
“…This fraction gets higher for complex scenes due to the presence of monocular cues [Harris and Watamaniuk 1995]. The sensitivity to the MID is poorly correlated with the sensitivity to frontoparallel motion, but it is well correlated with the static disparity sensitivity under different base disparity and defocus conditions [Cumming 1995].…”
Section: Motion In Depthmentioning
confidence: 95%